Tax Havens and their Role in International Tax Evasion Case of the Google’s Double Irish, Dutch sandwich - Dhaferi, Rima; Belkhiri, Mohammed Saadeddin (Finance and Business Economies Review, 2020)
Modern international tax evasion mechanisms rely on using tax havens, thus companies and prominent people develop new ways to use these places to their advantage. This paper aims to address the issue of tax evasion through tax paradises which is a, important phenomenon that causes a lot of damage to many countries and economies nowadays. In order to highlight the possible aspects of this phenomenon we relied on a case study of the Google company complex that uses a method known as double Irish and Dutch sandwich to reduce the tax burden and evade payment of its obligations